The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1007/s11205-019-02205-w
|View full text |Cite
|
Sign up to set email alerts
|

Post Materialism and Comparative Economic Development: Do Institutions Act as Transmission Channel?

Abstract: Although a growing number of countries are experiencing structural societal changes characterised by an increased prominence of post materialistic societal goals and personal values, there is limited empirical evidence on the economic effects of post materialism. In this paper, we address this gap in the literature by estimating the effect of post materialism on the level of economic development for a heterogeneous set of countries. Furthermore, in line with the notion that institutions may act as transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 85 publications
(118 reference statements)
0
14
0
Order By: Relevance
“…Kafka and Kostis (2021) finds a negative effect among OECD countries for the period 1981-2021, although they do not control for economic freedom, but for regulatory quality. Jordaan and Dima (2020) and Jordaan (2023) separate direct and indirect effects of post-materialism on economic growth and find the direct effect, which is measured after controlling for institutional quality, to be negative.…”
Section: Literature Review: the Puzzle Of Post-materialist Economic F...mentioning
confidence: 98%
See 1 more Smart Citation
“…Kafka and Kostis (2021) finds a negative effect among OECD countries for the period 1981-2021, although they do not control for economic freedom, but for regulatory quality. Jordaan and Dima (2020) and Jordaan (2023) separate direct and indirect effects of post-materialism on economic growth and find the direct effect, which is measured after controlling for institutional quality, to be negative.…”
Section: Literature Review: the Puzzle Of Post-materialist Economic F...mentioning
confidence: 98%
“…More generally, a higher level of post-materialism is associated with institutions, which then leads to higher economic growth. Jordaan and Dima (2020) finds a causality that runs from post-materialism to GDP per capita through institutional quality measured by the World Bank Governance Indicators (Kaufmann et al, 2010), while for Jordaan (2023) such an effect works through economic freedom. In both papers this indirect effect is positive: even after controlling for different possible determinants, a less materialist (a more post-materialist) country has institutions that are not only of higher quality but economically freer.…”
Section: Literature Review: the Puzzle Of Post-materialist Economic F...mentioning
confidence: 99%
“…The idea that the relation between social values and economic growth is mediated by institutions and economic freedom can be found in works of Johnson and Lenartowicz (1998), Williamson and Mathers (2011), Jordaan and Dima (2020) and Jora et al (2020). In addition to standard economic variables such as physical capital, human capital and innovation, non-standard variables such as geographic latitude, institutions, culture and social capital are considered important factors in explaining economic success (Roşca, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They also found that economic freedom is more important than culture in explaining economic growth. Jordaan and Dima (2020) analyzed the effect of post-materialism on economic development. They concluded that institutions are the channels of transmission for the indirect effects of social values.…”
Section: Introductionmentioning
confidence: 99%
“… Jordaan and Dima (2019), however, conclude that the negative effect is only the direct effect of post‐materialism. The indirect one works through institutions and increases growth.…”
mentioning
confidence: 99%